Retrospective analysis of scientific and psychological concepts of domestic violence (Bulletin of Kharkiv National University of Internal Affairs, 2023)
It is emphasised that in connection with the full-scale war of the russian federation against Ukraine, new risk factors for the increase in domestic violence have emerged, among which the most significant are fear, uncertainty; a sense of helplessness and confusion; socio-economic instability and job loss; forced displacement and loss of a safe environment and established interpersonal space; disruption of family dynamics and relationships; increased alcohol and drug use; easy access to various types of weapons; and the emergence of post-traumatic stress syndrome.It is noted that modern science considers domestic violence through the prism of existing approaches that explain the causes of its occurrence and peculiarities of its course.The first approach, the socio-cultural approach, focuses on the analysis of social structures, cultural norms and values of society as factors of domestic violence. It focuses on the impact of social factors and structures, as well as family relationships, on the management of the atmosphere of violence. The approach sees the main cause of domestic violence and violence against women as the so-called male dominance in social relations, the lack of gender equality, and the existence of established patriarchal norms that contribute to violence.The next individual psychological approach considers concepts that explain violence by human nature and focuses on the study of the personality traits of the perpetrator and the victim. Proponents of this approach emphasise that there are certain innate inclinations and instincts that push people to violence.Representatives of the systemic-family approach focus on the study of interaction, communication dynamics, conflict resolution processes in the family and ways of reconciliation that exist between its members. Violence is caused by various physical, moral, aesthetic, and economic constraints. According to scientists, violence is associated with the use of deliberate physical, psychological, financial and material pressure on a person, as most cases of domestic violence intersect with psychological pressure and exploitation.Representatives of the sociological approach note that violence is a general social phenomenon and it is a consequence of the clash of various interests manifested at different levels of its development, i.e. violence is socioculturally determined.The most widely accepted today is the ecological theory of violence, which explains domestic violence by considering the problem from different aspects through the prism of the mutual influence of four systems on human development: microsystem, mesosystem, exosystem, macrosystem.Therefore, despite the war, it is necessary to continue work on prevention and appropriate response to domestic violence, and understanding the essence and content of existing theoretical concepts of violence is one of the components of countering this phenomenon.
Keywords: domestic violence; victims; factors contributing to the increase in domestic violence; scientific approaches; concepts and theories of domestic violence; ecological theory of violence.